Unhealthy dietary patterns among healthcare professionals and students in Mexico - Alejandra Betancourt-Nuñez; Fabiola Márquez-Sandoval; Laura I. González-Zapata; Nancy Babio; Barbara Vizmanos (BMC Public Health, 2018)
Abstract Background While dietary patterns (DPs) enable the combination of foods that make up a person’s habitual diet to be known, little is known about the DPs of health sector professionals. The objective of this study was to describe the DPs of healthcare students and professionals and assess their association with sociodemographic, lifestyle, anthropometric and biochemical characteristics. Methods Cross-sectional design. A sample (n = 319) of healthcare students and professionals in apparent good health who studied or worked at the University of Guadalajara (Mexico) was selected. A semiquantitative food intake frequency questionnaire validated on a Mexican population was administered. Questions covering sociodemographic factors, smoking habits and physical activity were asked. Weight, height, waist circumference, blood pressure, triglycerides, glucose, HDL-cholesterol, LDL-cholesterol and total cholesterol were also measured. DPs were generated from a principal components analysis of 25 food groups, and associations were analyzed using logistic regression adjusted for age and sex. Results The majority of participants were younger than 29 years (84%), women (71.2%) and students (59.6%). Three DPs were identified: “Traditional Westernized”, “Healthy” and “Animal protein and alcoholic beverages”. After adjustment, the “Traditional Westernized” DP was positively associated with being younger than 22 years (OR: 2.15; 95%CI: 1.1–4.1); the “Healthy” DP was positively associated with having a daily energy expenditure from physical activity greater than 605 kcal (OR: 4.19; 95%CI: 2.3–7.5), and it was negatively associated with being younger than 22 years (OR: 0.48; 95%CI: 0.2–0.9); and the “Animal protein and alcoholic beverages” DP was positively associated with being male (OR: 3.07; 95%CI: 1.8–5.1) and a smoker (OR: 2.77; 95%CI: 1.2–6.3). No association was found between DPs and anthropometric and biochemical characteristics. Conclusions Among the participants evaluated, healthy DP was associated with being physically active while unhealthy DPs were associated with being younger than 22 years, male and a smoker. These data suggest that being knowledgeable about health does not ensure that individuals will engage in healthy behaviors. As is the case among the general population, training and individual efforts aimed at achieving healthy behaviors must be reinforced by initiatives undertaken by social groups, social institutions, the community at large as well as political and business leaders.